Acidentes de trabalho notificados em um hospital de urgência e emergência no município de Belém-Pará - BEZERRA, André Abelardo Batista (2022)
The occupational industrial accidents and illnesses approximately kill in Brazil 60 a thousand people per year, in accordance with data of the International Organization of the Work. This work aims at to describe the profile of the rough workers and the work accidents, taken care of in the Municipal Hospital and First Aid Clinic (HPSM) of Belém-Pará Dr Mário Pinotti, in the period of January of 2003 the December of 2005. A retrospective descriptive study was carried through, through the extracted collection of data of the form of Communication of Work Accidents informed in the HPSM in the period of study. The analyzed variable had been sex; age; civil state; filiation to the social welfare; retirement; sector and the economic activity developed by the company; month and year of occurrence of the accident; place, area, city and state where the accident occurred; type of accident; police register and death; part of the reached body; type of injury suffered for the victim; occurrence of hospital internment and removal of the work. The data had been analyzed through the Excel program version 3.0. The results shows 1.951 cases of workers accidents had been observed, of which 92.67% were of the masculine sex, with average of age of 33,77 years old, and with age varying from 20 to 29 years old (39.88%), 62.94% were single, 94.31% employed workers and 1.23% were pensioners. The branch of more frequent activity was of civil construction (27.06%) and the secondary sector contributed with 53,82% of the cases. The typical accident was responsible for 84,73% of the cases and the localization of the accident occurred, in its majority, the establishment of the employer (61.30%). The superior limbs (40.97%) had constituted the region of the body more attack and the wounds (24.91%), in general, had been the more common types of injury. In relation to the gravity of the event, 15.74% had needed hospital internment, 91.39% had been moved away from the work and 0.82% had evolved the death. The results show that the works accidents are a great problem of public health, due to gravity of the injuries, to the removal of the activities of work and to the generated incapacity, presenting serious partner-economic implications. Another question notable is the enormous difficulty in if getting consistent information as for the accidents. With base in these data, salient it necessity of improvements in the systems of notification of the cases aiming at to subsidize the authorities politics of the health in the planning of action in the areas of the security, protection to the health and prevention of illnesses and injuries.